Knowledge and Preventive Behavior Toward Gastroesophageal Reflux Disease Among Undergraduate Students at Universitas Gadjah Mada - Dayinta, Adella; Widayanti, MPH., Apt., Ph.D., Anna Wahyuni (Rumah Sakit Akademik Universitas Gadjah Mada, 2025)
Background: Gastroesophageal Reflux Disease (GERD) is a chronic condition characterized by the regurgitation or backflow of stomach contents into the esophagus, which can potentially lead to various complications. This study aims to evaluate the relationship between the level of knowledge and the level of preventive behavior regarding GERD among students at Universitas Gadjah Mada.Materials and methods: A cross-sectional study was conducted using a convenience sampling method, involving 113 students aged 18-25 years, with data collected through a questionnaire. Knowledge about GERD was measured using the Guttman scale, while preventive behavior was assessed using the Likert scale.Results: The results revealed a significant relationship between knowledge and preventive behavior (Pearson Chi-Square value: 8.817, p=0.03). Among the 49 students with poor knowledge, 59.2% exhibited poor preventive behaviors, while 68.8% of the 64 students with good knowledge demonstrated good preventive behaviors.Conclusion: Overall, students with better knowledge of GERD tend to have better preventive behaviors. The study also found a relationship between the academic cluster with levels of knowledge and preventive behaviors. However, other characteristics such as age, sex, semester, history of GERD, living situation (alone or with parents), and monthly allowance were not significantly associated.